Analisis Pengembangan Masyarakat Transmigran Di Satuan Pemukiman Saluandeang Kabupaten Mamuju Tengah, Provinsi Sulawesi Barat - Poespaningroem, Diah Eka (Syntax Corporation, 2025)
The Transmigration Program has been made a priority in long-term development in Indonesia with the hope of improving the quality of life of transmigrants and indigenous peoples in the destination area. Transmigration is part of the national transmigration program that aims for equitable regional development and is one of the ones that has experienced a significant impact from this program in the Saluandeang Transmigration Settlement Unit, Central Mamuju Regency, West Sulawesi Province. The challenge of the Saluandeang Transmigration Settlement Unit is the problem of transmigrants, both immigrants and local/local communities who become transmigrants, do not receive skills training at the location of the transmigration destination, so that transmigrants do not have the skills to cultivate transmigration land into productive land that can improve the welfare of transmigrants. In addition, transmigrants have not been able to adapt to the new environment, so there is a desire to leave the transmigration location and the land given to transmigrants has not been able to be processed properly and there is a conflict/occupation with the local community. Although there have been some achievements socially and economically, challenges remain, especially in terms of providing training to transmigrants after placement in new transmigration locations, to be able to be independent by having the ability to have skills that can cultivate the land given to transmigrants both to transmigrants from the area of origin and local transmigrants. The success of transmigration programs in the future will depend largely on how these challenges are addressed with a more inclusive and sustainable approach